The feasibility of biogeochemical and geobotanical prospecting at Spargoville, Western Australia : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Chemistry at Massey University - Nielsen, Jeppe Søndergaard (Massey University, 1972)
Several plant species together with their associated soils from Spargoville, Western Australia, were analysed for chromium, copper, cobalt, manganese, nickel and zinc by atonic absorption spectrophotometry. Particular reference was given to nickel and copper to evaluate the usefulness of plant analysis for biogeochemical prospecting. The nickel content in the soils gave plateaus of high values over ultrabasic rock types whereas the copper levels in the soils gave peaks over areas of mineralization at ultrabasic contacts. Consideration of the plant data showed that each species accumulated different amounts of the above elements, and that they distributed these trace elements in different ways between their leaves and twigs, or between their bark and wood. Relationships between nickel and copper concentrations in the plants and in the soils were evaluated by computing correlation coefficients; promising statistical results were checked graphically. The nickel and copper concentrations in the bark of Eucalyptus lesouefii most accurately depicted the concentrations of these metals in the soils. It was also found that the barks of Eucalyptus lesouefli, Eucalyptus longicornis and Eucalyptus torquata could be used together for prospecting purposes. In the cases where the soil-plant relationship was either very good or very poor, it seemed to make no difference whether parametric or non-parametrie correlation coefficients were used. When the relationship was intermediate between these extremes, however, the non-parametric statistic was superior. A geobotanical study was also carried out tn determine whether the distributions of the plant species was related to the geolory. Dodonaea lobulata. Pittosporum phillyraeoides and Trymaliun ledifolium were found to grow only on ultrabasic rook types, and the outer, black bark of E. lesouefii growing in mineralized ground was observed to grow to a greater height on the trunk than occurred when this species grew in non-raineralized soils. when discriminant analysis was applied to plant mapping data, the different rock types could be effectively discriminated using the relative abundances of as few as one-third of the species present. These results were markedly superior to those obtained when discriminant analysis was applied to some biogeochemical data.
Keywords: Western Australia Spargoville; Biogeochemical prospecting; Geobotanical prospecting; Nickel content; Copper content; Soils